UMP strives for excellence - Abdul Razak, Raaff; T.N., Alagesh (The New Straits Times Press (M) Bhd., 2018)
Prof. Datuk Seri Dr. Daing Nasir Ibrahim, the internationalisation of UMP in building a strong academic network of cooperation with the Federal Republic of Germany has resulted in globally competitive graduates that standout and match up to not only German companies but also companies with business relationships with Germany.